2020
DOI: 10.5194/acp-20-10997-2020
|View full text |Cite
|
Sign up to set email alerts
|

Development of aerosol activation in the double-moment Unified Model and evaluation with CLARIFY measurements

Abstract: Abstract. Representing the number and mass of cloud and aerosol particles independently in a climate, weather prediction or air quality model is important in order to simulate aerosol direct and indirect effects on radiation balance. Here we introduce the first configuration of the UK Met Office Unified Model in which both cloud and aerosol particles have “double-moment” representations with prognostic number and mass. The GLObal Model of Aerosol Processes (GLOMAP) aerosol microphysics scheme, already used in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 96 publications
2
36
0
Order By: Relevance
“…In our previous model evaluations, although the model is generally able to well simulate the horizontal and vertical distribution of aerosols in the SEA, aerosols are slightly underestimated at higher altitudes and overestimated west of 5 °W (Che et al, 2021). The latter is also confirmed by studies with the same model (though with different configurations), which also shown an overestimation of aerosol concentrations in the western part of SEA (Gordon et al, 2020;Ranjithkumar et al, 2021). These model biases introduce some uncertainties into our results, particularly with respect to the effects of BB aerosols on CCN and clouds.…”
Section: Discussionsupporting
confidence: 59%
“…In our previous model evaluations, although the model is generally able to well simulate the horizontal and vertical distribution of aerosols in the SEA, aerosols are slightly underestimated at higher altitudes and overestimated west of 5 °W (Che et al, 2021). The latter is also confirmed by studies with the same model (though with different configurations), which also shown an overestimation of aerosol concentrations in the western part of SEA (Gordon et al, 2020;Ranjithkumar et al, 2021). These model biases introduce some uncertainties into our results, particularly with respect to the effects of BB aerosols on CCN and clouds.…”
Section: Discussionsupporting
confidence: 59%
“…Global bulk aerosol models and empirical representations of aerosol indirect effects are being replaced with microphysical aerosol models such as ECHAM5-HAM (Stier et al, 2005) and GLOMAP (also known as UKCA mode) (e.g. Mann et al, 2010;Bellouin et al, 2013), and more explicit representations of cloud and precipitation processes (Hill et al, 2015;Grosvenor et al, 2017) have also been developed. Such schemes require extensive evaluation, which is often achieved through multi-model intercomparison studies (e.g.…”
Section: Aerosol-cloud Interactions (Aci)mentioning
confidence: 99%
“…The single-moment cloud microphysics scheme will also be replaced by the Cloud-AeroSol Interacting Microphysics (CASIM) scheme in DM-Chem, where both cloud and aerosol particles have double-moment representations with prognostic number and mass. This scheme has been implemented for fog in large eddy simulations by Poku et al (2019) and coupled to GLOMAP by Gordon et al (2020). Finally, the visibility scheme needs improvement, for example a more sophisticated representation of the extinction efficiency Q.…”
Section: Discussionmentioning
confidence: 99%
“…(2019) and coupled to GLOMAP by Gordon et al . (2020). Finally, the visibility scheme needs improvement, for example a more sophisticated representation of the extinction efficiency Q .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation